A Narrative Engineering Model of Deli Serdang Regency Folk Tales for Bullying Mitigation - Atika Wasilah; Achmad Yuhdi; Hidayat Herman (LingPoet: Journal of Linguistics and Literary Research, 2026)
This study aims to identify, analyze, and engineer the narratives of folktales from Deli Serdang Regency as an effort to strengthen anti-bullying values. This research employs a qualitative approach using a content analysis method on folktales collected through documentation studies and local narrative sources. The research data consist of four folktales: Panglima Denai, Batang Kuis, Sri Putih Cermin, and Asal Mula Sungai Ular. The findings reveal that the four folktales contain character values relevant to bullying prevention, including empathy, respect for differences, self-control, and peaceful conflict resolution. The analysis of narrative structures indicates that the social conflicts presented in the stories are associated with character differences, coercion, power dominance, and teasing behavior. These conflicts are resolved through moral values emphasizing mutual respect and justice. Furthermore, narrative engineering was conducted by strengthening social conflicts and moral values without altering the fundamental structure of the folktales. Based on this process, a narrative engineering model was developed, consisting of folktale identification, narrative structure analysis, social conflict engineering, and the reinforcement of moral values. This model produced folktales that are more contextualized to bullying issues while preserving local wisdom. Therefore, the folktales of Deli Serdang Regency have significant potential as a source of character education, particularly in preventing bullying through a narrative engineering approach.